The impact of low carbon warehouse practices on operational excellence : the mediating impact of green innovation capabilities - Azian, Ibrahim (2023)
The emerging environmental awareness of the public and the implementation of governmental regulations force organizations to employ environmental practices such as low carbon warehouse (LCW) practices and green innovation (GI). Both practices are important to achieve operational excellence (OE). OE enables an organization to gain a competitive advantage. By adopting LCW practices, companies in the manufacturing industry can improve their overall OE. However, research on the relationship between LCW practices, GI, and OE is relatively rare. Thus, this exploratory sequential mixed methods research is carried out and this study aims to provide empirical evidence showing that LCW practices and GI capabilities significantly improve companies' OE in order to encourage manufacturing companies to implement LCW practices. In addition, this study investigates the relationship between LCW practices and GI capabilities and the effects of these practices on companies OE in 160 manufacturing companies in Malaysia. The results of PLS-SEM revealed that there is a significant and positive relationship between LCW practices, GI capabilities, and OE. Moreover, GI capabilities had a positive effect on companies OE. Furthermore, GI capabilities had a mediating relationship between LCW practices and companies OE. Therefore, the present study confirmed the significant influence of LCW practices on boosting the GI of organizations and on the manufacturing establishment, which eventually improves the environment. In brief, the outcomes of this study provide an enhanced understanding of the significant role of GI in the manufacturers for improving their LCW practices and companies' OE. The comprehensive LCW model in this study has also been empirically tested to be reliable and valid. This would help manufacturing companies meet environmental performance and operational performance through LCW practices.